Zapomniane zwycięstwo 4 czerwca — o mitologii politycznej filmu „Psy” Władysława Pasikowskiego - Nieć, Mateusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article analyzes the victorious election of Solidarity on 4 June 1989. Władysław Pasikowski, a young Polish director, has shown in the movie Dogs 1992 a metaphor of the 4 June victory, which is analyzed in this article. Other issues from the movie are not presented, neither is the contemporary political situation. Only the contemporary context of the movie is presented. The movie Dogs shows a wide political and cultural background of a political change, probably because Pasikowski is a cultural anthropologist, not only a director. The article consists of three parts. In the first part of the article I present a concept of mythology by Roland Barthes in my own interpretation; I named my interpretation a political mythology. In the second part of the text I explain the phrase “forgotten victory” and discuss the political context “forgetfulness”. In the last part of the article I analyze the movie Dogs. Pasikowski presented a story of a police officer and his community political police during transformation in Poland. Pasikowski showed in the film the last days of the People’s Poland, her moral and political downfall. This film gave rise to many voices and commentaries, both positive and disapproving. The film was recognized by victims fighting about liberty as hurtful. Especially, a scene in a policemen canteen was recognized as derogatory. In a few scenes of the movie Pasikowski described the elite of People’s Poland. Pasikowski told a story about the last days of People’s Poland in the context of a crime. Since the movie Dogs, Pasikowski has debated with the Polish Film School and at the same time he has carried on with moral issues of the Polish Film School. He said and showed where the winners of Maciek Chełmicki, the protagonist of the film Popiół i diament Ashes and Diamonds of Andrzej Wajda director and Jerzy Andrzejewski writer, are now. Moreover, Pasikowski has discussed in films with Polish right-wing parties and right-wing journalists about the beginning of the Third Republic of Poland.
Keywords: mitologia polityczna; film Psy; transformacja w Polsce; 4 czerwca 1989 r.; Solidarność; Polska Ludowa; III Rzeczpospolita Polska